Comparative Characteristics of Cardiac Rate in Rats When Applying Different Methods of Cold Effects - Babijchuk, V. G. (Problems of Cryobiology and Cryomedicine, 2007)
Comparative characteristics of cardiac rate in rats of different age groups, cooled by both methods of standard extreme cryotherapy and rhythmic one, proposed by the author, have been presented. Negative chronotropic effect after norepinephrine intraperitoneal introduction into rats is observed only after the 9th cooling session by the standard method and after the 3rd one if cooling with the rhythmic effects, that might testify to earlier terms of blood brain barrier (BBB) permeability for neuromediator. This may be confirmed by pinocytosis activation in capillary endotheliocytes, as well as by revealing the horse radish peroxidase granules in endotheliocyte fragments of cerebral capillary.